Maximal cardiorespiratory responses in exhaustive tandem-bicycle ergometer exercise - Comparison of the subjects with the different peak oxygen uptake - Onodera, S.; Katayama, K.; Ogita, F.; Saito, T.; Hayashi, S.; Murata, M.; Wada, T.; Goto, M.; Watanabe, Y.; Yosioka, A.; Nishimura, K.; Kremenic, M. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Purpose: We have reported that the tandem-bicycle ergometer is a suitable apparatus to give an equal load to two subjects from submaximal exercise to exhaustion in the viewpoint of cardiorespiratory responses (Onodera S. et al., ECSS 2012, 2013). This time, we tested whether maximal cardiorespiratory responses of two subjects obtained during tandem-bicycle exercise are the same as those during single-bicycle exercise, even when two subjects with different peak oxygen uptake (VO2peak) performed exhaustive tandem-bicycle exercise. Methods: First, fourteen healthy young Japanese males performed incremental single-bicycle exercise until exhaustion (SIN), and VO2peak and peak heart rate (HRpeak) were recorded. Then, the subjects were divided into two groups; one was high VO2peak group (high group; n=7), and the other was low VO2peak group (low group; n=7). The difference in VO2peak between groups was around 10%. Next, the incremental exhaustive tandem-bicycle exercise was carried out in two different conditions, i.e., the former saddle (FOR) and the rear saddle (REA) trial. Two subjects for tandem-bicycle exercise were randomly selected for each group. In the test, VO2peak and HRpeak were determined. Results and Discussion: VO2peak and HRpeak in the SIN trial were 46.6 ± 2.7 ml/kg/min and 195.1 ± 9.5 bpm in the high group, and 41.2 ± 3.0 ml/kg/min and 193.0 ± 9.5 bpm in the low group. In the FOR and REA trials of the high group, VO2peak and HRpeak were 45.4 ± 2.8 ml/kg/min and 191.1 ± 8.2 bpm (FOR), and 44.8 ± 3.5 ml/kg/min and 190.9 ± 8.6 bpm (REA), respectively. In the low group, VO2peak and HRpeak were 41.5 ± 2.9 ml/kg/min and 190.6 ± 9.2 bpm (FOR), and 41.7 ± 3.6 ml/kg/min and 191.1 ± 7.9 bpm (REA). When VO2peak and HRpeak among three conditions, i.e. single-trial, the FOR and REA in tandembicycle trial, were compared within each group, no significant differences were found. In conclusion, it is suggested that even if there are 10% difference in VO2peak between the subjects, maximal cardiorespiratory responses of the two subjects during tandem-bicycle exercise are the same as those during single-bicycle exercise.